Immunoglobulin kappa deleting element rearrangements are candidate targets for minimal residual disease evaluation in mantle cell lymphoma. Issue 5 (28th August 2020) - Della Starza, Irene; De Novi, Lucia Anna; Cavalli, Marzia; Novelli, Noemi; Soscia, Roberta; Genuardi, Elisa; Mantoan, Barbara; Drandi, Daniela; Ferrante, Martina; Monitillo, Luigia; Barbero, Daniela; Ciabatti, Elena; et al.
Abstract: Minimal residual disease (MRD) assessment is of high clinical relevance in patients with mantle cell lymphoma (MCL). In mature B‐cell malignancies, the presence of somatic hypermutations (SHM) in Variable‐Diversity‐Joining Heavy chain (VDJH) rearrangements leads to frequent mismatches between primers, probes, and the target, thus impairing tumor cells quantification. Alternative targets, such as immunoglobulin kappa‐deleting‐element ( IGK‐Kde ) rearrangements, might be suitable for MRD detection. We aimed at evaluating the applicability of IGK‐Kde rearrangements for MRD quantification in MCL patients by real‐time quantitative polymerase chain reaction (RQ‐PCR)/digital‐droplet‐PCR (ddPCR). IGK screening was performed on bone marrow samples from two cohorts: the first from Turin (22 patients enrolled in the FIL‐MCL0208 trial, NCT02354313) and the second from Rome (15 patients). IGK‐Kde rearrangements were found in 76% (28/37) of cases, representing the sole molecular marker in 73% (8/11) of IGH‐BCL1/IGH negative cases. MRD RQ‐PCR monitoring was possible in 57% (16/28) of cases, showing a 100% concordance with the conventional targets. However, the frequent background amplification affected the sensitivity of the assay, that was lower in MCL compared to acute lymphoblastic leukemia and in line with multiple myeloma published results. ddPCR had a good concordance with RQ‐PCR and it might help to identify false positive/negative results. From a clinical perspective, we suggest that IGK‐Kde can be a candidate target for MRD monitoring and deserves a validation of its predictive value in prospective MCL series.